2005
DOI: 10.1007/s10789-005-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bi Doping on the Optical Properties of CdI2

Abstract: The effect of Bi impurity on the optical absorption and roentgeno-, photo-, and thermoluminescence spectra of CdI 2 crystals grown by the Bridgman-Stockbarger method is studied. CdI 2 activation with BiI 3 produces a number of absorption bands related to electronic transitions of Bi 3+ . Bi produces no emission centers in CdI 2 . The 550-to 560-nm luminescence of CdI 2 is due to the radiative recombination of self-trapped anion excitons. The observed changes in spectral distribution and the reduction in light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The ionic cores are represented by ultrasoft pseudopotentials for Cd and I atoms. The Cd 4d 10 , 5s 2 , and I 5s 2 , 5p 5 electrons are explicitly 3 Results and discussion 3.1 Geometry and structure optimization The ground-state properties of trigonal CdI 2 are investigated and the total energy is fitted to the third-order Birch-Murnaghan equation [22] to obtain equilibrium lattice constants. The variation in the total energy as a function of volume is shown in Fig.…”
mentioning
confidence: 99%
“…The ionic cores are represented by ultrasoft pseudopotentials for Cd and I atoms. The Cd 4d 10 , 5s 2 , and I 5s 2 , 5p 5 electrons are explicitly 3 Results and discussion 3.1 Geometry and structure optimization The ground-state properties of trigonal CdI 2 are investigated and the total energy is fitted to the third-order Birch-Murnaghan equation [22] to obtain equilibrium lattice constants. The variation in the total energy as a function of volume is shown in Fig.…”
mentioning
confidence: 99%
“…Due to peculiarities of the structural arrangement of CdI 2 there are specific ways of the incorporation of impurities or overstoichiometric Cd atoms into the crystal lattice. Therefore, a number of reports were devoted to the studies of doped CdI 2 crystals and crystals with excess of cadmium (see [2][3][4]). In particular, as demonstrated earlier [5], interesting changes in optical absorption are observed when CdI 2 is doped with BiI 3 (which is another layered compound).…”
Section: Introductionmentioning
confidence: 99%
“…Activating or uncontrolled impurities caused the observed slight shift of the TSL peak maxima. The nature of the trapping centers responsible for the separate TSL peaks of the CdI 2 crystals has been discussed [30][31][32]. The experimental results and the literature indicated that the positions of separate peaks in the studied CdI 2 :Eu crystal phosphors and crystals based on CaF 2 [22,33] depended little on the cationic dopant.…”
mentioning
confidence: 99%